Quality characteristics and nutrient yield of fodder maize (Zea mays) as influenced by seeding density and nutrient levels in Indo-Gangetic Plains - KUMAR, RAKESH; SINGH, M; MEENA, B S; KUMAR, SOURABH; YADAV, M R; PARIHAR, C M; RAM, H; MEENA, R K; MEENA, V K; KUMAR, U (The Indian Journal of Agricultural Sciences, 2017)
Productivity and quality traits of forage crops are largely affected by agronomic management at field conditions in different climatic strata. Therefore, the present field investigation was carried out during kharif season of 2014 and 2015 at ICAR-NDRI, Karnal to evaluate the effect of different planting densities and fertility levels on nutritive yields and quality of fodder maize (Zea mays L.). An experiment was laid out in split plot arrangement with three treatments in main-plot of planting densities of 60, 75 and 90 kg seed/ha and six treatments in subplot of nutrient levels, i.e. 0, 50, 75, 100, 125 and 150% recommended dose of fertilizer (RDF), i.e. 120 kg N/ha and 60 kg P2O5/ha. All the seed rates were found statistically at par for all the parameters except fiber fractions, i.e. neutral detergent fiber (NDF), acid detergent fiber (ADF) and acid detergent lignin (ADL) content, in which 60 kg/ha seed rate accumulated significantly lower fiber contents. However, numerically higher values of fodder yields and quality parameters were observed at lower planting density. Nutrient levels showed significant increase in fodder yields with increase in dose of fertility up to 125% RDF. The combined use of 60 kg/ha seed rate and 125% RDF obtained significant maximum green (61.7 t/ha) and dry fodder yield (14.1 t/ha). The results showed that use of 150% RDF improved CP content by 20.2%, ether extract by 20.1% and ash content by 23.3% over control. Further, the maize fodder supplied with 150% RDF attributed minimum level of fiber fractions and magnitude of reduction in NDF was 3.49%, ADF was 3.54% and that of ADL was 7.65% in comparison to 0% RDF. The combination of 60 kg/ha seed rate and 125% RDF obtained significant maximum CP (1542.1 kg/ha), EE (367.4 kg/ha) and ash yield (1280.0 kg/ha). The use of 150% RDF also resulted into improvement in the nutrient content to the tune of 20.2% in N and 12.5% in P and enhanced nutrient uptake by 50.5% of N and 41.9% that of P over control. It can be concluded that to realize higher productivity with enhanced quality of fodder maize with optimum density (60 kg/ha) and use of 125% of RDF are quite helpful, which will further strengthen and sustain the performance of livestock in terms of health and milk production.